Protein disulfide isomerase A6 promotes the repair of injured nerve through interactions with spastin - Luo, Jianxian; Xie, Min; Peng, Cheng; Ma, Yanming; Wang, Ke; Lin, Gengxiong; Yang, Hua; Chen, Tianjun; Liu, Qiuling; Zhang, Guowei; Lin, Hongsheng; Ji, Zhisheng (Frontiers in Molecular Neuroscience, 2022)
The maintenance of appropriate endoplasmic reticulum (ER) homeostasis is critical to effective spinal cord injury (SCI) repair. In previous reports, protein disulfide isomerase A6 (PDIA6) demonstrated to serve as a reversible functional modulator of ER stress responses, while spastin can coordinate ER organization through the modulation of the dynamic microtubule network surrounding this organelle. While both PDIA6 and spastin are thus important regulators of the ER, whether they interact with one another for SCI repair still needs to be determined. Here a proteomics analysis identified PDIA6 as being related to SCI repair, and protein interaction mass spectrometry further confirmed the ability of PDIA6 and spastin to interact with one another. Pull-down and co-immunoprecipitation assays were further performed to validate and characterize the interactions between these two proteins. The RNAi-based knockdown of PDIA6 in COS-7 cells inhibited the ability of spastin to sever microtubules. PDIA6 was also found to promote injured neuron repair, while spastin knockdown reversed this reparative activity. Together, these results thus confirm that PDIA6 and spastin function together as critical mediators of nerve repair, highlighting their potential value as validated targets for efforts to promote SCI repair.